View of the west-facing elevation of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the west-facing elevation of the Bhandasar Temple. The wall is marked by pillars at the two corner ends and the bays of the wall are separated by pilasters. The walls have long windows from the base level, which can also be called doorways. These open from the inside of the mandapa (pillared hall). The pillars and pilasters are identical in design. They have a wider base and slender and relatively plain surfaces but slight vertical offsets on the corners of the shaft. These are ornamented with floral capitals and brackets.